Arrestin-3 differentially regulates platelet GPCR subsets. (3rd July 2020) - Hutchinson, James L.; Zhao, Xiaojuan; Hill, Rob; Mundell, Stuart J.
Abstract: The principal demonstrated role of the nonvisual arrestins in vivo is to limit G protein-coupled receptor (GPCR) signaling. Nonetheless, a direct demonstration of this fundamental ability in platelets remains lacking, despite the prominent role played by GPCRs in platelet activation. This paper describes the basic characterization of the activatory responses of platelets from mice lacking arrestin-3 (arr3-/-), revealing pleiotropic roles dependent on GPCR ligand. Functionally, arrestin-3 acts as a brake on platelet aggregation regardless of ligand tested. Downstream of P2Y receptors, arr3-/- mice show increased secretion and integrin activation mirrored by enhanced intracellular calcium signaling and global PKC-dependent phosphorylation. Furthermore, P2Y12 receptor (P2Y12R) activity as assessed by ADP-mediated reduction of VASP phosphorylation is enhanced in arr3-/-mice. Downstream of PAR receptors there are similar increases in secretion and integrin activation in arr3-/- mice, together with enhanced PKC activity. Last, in arr3-/- mice the TP receptor displays unaltered PKC activity but markedly reduced calcium responses, which together with the kinetics of the aggregation response suggested a unique positive regulatory role for arrestin-3 in TP signaling. Overall, this paper reveals pleiotropic roles for arrestin-3 dependent on GPCR ligand describing for the first time a negative regulatory function for arrestin-3 in platelets.